NALCN expression is down-regulated and associated with immune infiltration in gastric cancer - Li, Xuewei; Wu, Na; Wang, Chen; Pei, Beibei; Ma, Xiaoyan; Xie, Jun; Yang, Wenhui (Frontiers in Immunology, 2025)
BackgroundNALCN has been identified as a tumor suppressor gene, and its role in human cancer progression has garnered significant attention. However, there is a paucity of experimental studies specifically addressing the relationship between NALCN and immune cell infiltration in gastric cancer (GC).MethodsThe expression levels of NALCN in tumor tissues, peripheral blood and gastric cancer cells lines from patients with GC were assessed using RNA sequencing, immunohistochemistry (IHC) staining and RT-qPCR. Data obtained from the Gene Expression Omnibus (GEO) and The Cancer Genome Atlas (TCGA) databases were utilized to investigate the correlation between NALCN expression and immune cell infiltration in GC. Subsequently, the relationship between NALCN expression and infiltrating immune cells in GC tissues was examined through immunofluorescence method. Additionally, in vitro experiments were conducted to evaluate the impact of NALCN knockdown on T cells function in GC cell lines.ResultsRNA sequencing analysis revealed that NALCN expression was significantly downregulated in GC tissues. Specifically, NALCN levels were lower in GC tumor tissues and plasma compared to adjacent non-tumor tissues and healthy controls. Consistent with these findings, the expression trend of NALCN mRNA in the GEO database mirrored the experimental results. Mechanistically, NALCN knockdown markedly enhanced cell proliferation, colony formation and migration while reducing apoptosis rates in AGS and GES-1 cells. Analysis of the TCGA database indicated a positive correlation between NALCN expression and the infiltration of B cells, cytotoxic cells, immature dendritic cells (iDC) cells, CD8+ T cells, and others in GC tissue. Conversely, Th17 and Th2 cells infiltration exhibited a negative correlation with NALCN expression. Immunofluorescence staining confirmed that B cells and CD8 T cells were more abundant in GC tumor tissues with high NALCN expression, whereas Th17 and Th2 cells were less prevalent. Subsequently, we co-cultured GC cells transfected with NALCN knockdown or control vectors along with their supernatants with T cells. The results demonstrated that NALCN knockdown in GC cells or their supernatants inhibited T cell proliferation compared to control conditions. Moreover, NALCN may play a role in glucose and glutamine uptake.ConclusionsNALCN facilitates immune cell aggregation in GC and has potential as a biomarker for immune infiltration.